7Be/210Pbxs Ratio-Derived Age and Residence Time of Suspended Sediments in Galveston Bay - Schmidt, Nicole; Dellapenna, Timothy; Lin, Peng (Frontiers in Marine Science, 2021)
The winds associated with the passage of meteorological fronts cause waves that induce sediment remobilization/resuspension, especially within shallow estuaries such as Galveston Bay. The passage of cold fronts, collectively, on an annual to decadal basis, generate more sediment resuspension than most hurricanes and tropical storms. With a warming climate, the intensity of all meteorological events is shifting toward having greater impacts on these biologically productive environments. To better understand sediment resuspension within the bay, water samples were collected during frontal passages at two locations in Galveston Bay, including one location in the middle portion of the bay and another closer to the mouth of the bay. By collecting precipitation, water samples in both the middle and lower bay, and measuring the ratio of 7Be/210Pbxs in these samples; we quantified the residence times of total suspended sediment (TSS) in middle and lower Galveston Bay. Our results showed that suspended sediment age increased and percent of new suspended sediment decreased along the axis from the middle bay to the lower bay. This results from the initial introduction of newly labeled isotopes and suspended load coming from fluvial discharges which enter at the top of the bay and travel through the bay. The age of suspended sediment from the first sampling event was 70 ± 10 days, whereas the age in the second event was 16 ± 3 days greater. In the last sampling event, the age of suspended sediment event was 35 ± 7.4 days younger than the second, suggesting that the majority of suspended sediments was likely transported entirely out of the bay by the second cold front, prior to the final sampling event. This indicates that there are longer suspended sediment residence times when the water is trapped within the bay. Our estimated residence time of suspended sediments (51–105 days) suggest the particle-bound contaminants adsorb to suspended sediment may spend months suspended in the bay before exiting the bay or being accreted into the bay sediment column, increasing the exposure time of living organisms to various particle-bound contaminants.